The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1124/mol.111.071043
|View full text |Cite
|
Sign up to set email alerts
|

Selective Toxicity of the Anthelmintic Emodepside Revealed by Heterologous Expression of Human KCNMA1 inCaenorhabditis elegans

Abstract: Emodepside is a resistance-breaking anthelmintic of a new chemical class, the cyclooctadepsipeptides. A major determinant of its anthelmintic effect is the calcium-activated potassium channel SLO-1. SLO-1 belongs to a family of channels that are highly conserved across the animal phyla and regulate neurosecretion, hormone release, muscle contraction, and neuronal network excitability. To investigate the selective toxicity of emodepside, we performed transgenic experiments in which the nematode SLO-1 channel wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…Orthologues of slo-1 from parasitic nematodes also restore emodepside sensitivity to the C. elegans loss-of-function mutants [78]. In contrast, a human orthologue of slo-1 does not confer emodepside sensitivity to these mutants, though it does rescue some of the behavioral deficiencies associated with the absence of the channel [79]. Electrophysiological studies on Ascaris suum are consistent with emodepside activation of SLO-1, but with a slow time course, possibly indicative of a non-extracellular binding site within the transmembrane domains [80].…”
Section: Nematode Slo-1 Ca2+-activated Potassium Channels As Targets mentioning
confidence: 99%
“…Orthologues of slo-1 from parasitic nematodes also restore emodepside sensitivity to the C. elegans loss-of-function mutants [78]. In contrast, a human orthologue of slo-1 does not confer emodepside sensitivity to these mutants, though it does rescue some of the behavioral deficiencies associated with the absence of the channel [79]. Electrophysiological studies on Ascaris suum are consistent with emodepside activation of SLO-1, but with a slow time course, possibly indicative of a non-extracellular binding site within the transmembrane domains [80].…”
Section: Nematode Slo-1 Ca2+-activated Potassium Channels As Targets mentioning
confidence: 99%
“…Initial slo -1 pharyngeal expression experiments in slo-1 null-mutants, did not detect effects of emodepside on the frequency of pharyngeal pumping. However, Crisford et al (2011) subsequently described how ectopic over-expression of SLO-1a in C. elegans pharyngeal muscle did, in fact, give rise to sensitivity of the pharyngeal muscle to emodepside. Crisford et al (2011) also described transgenic experiments in which the C. elegans SLO-1a channel was swapped for KCNMA1, the human orthologue.…”
Section: 1 Different Mode Of Actionmentioning
confidence: 99%
“…However, Crisford et al (2011) subsequently described how ectopic over-expression of SLO-1a in C. elegans pharyngeal muscle did, in fact, give rise to sensitivity of the pharyngeal muscle to emodepside. Crisford et al (2011) also described transgenic experiments in which the C. elegans SLO-1a channel was swapped for KCNMA1, the human orthologue. Interestingly, the sensitivity to emodepside in the rescues depended upon origin of the SLO-1 channel: the human KCNMA1 channel was 10–100 time less sensitive to emodepside than the rescues expressing C. elegans SLO-1a channel.…”
Section: 1 Different Mode Of Actionmentioning
confidence: 99%
“…Following a screen to identify C. elegans mutants resistant to emodepside, it was found that worms with loss-of-function mutations in slo-1, a gene that encodes a voltage-and calcium-activated potassium, or BK, channel (Atkinson et al, 1991), are resistant to emodepside inhibition of locomotion and pharyngeal pumping whereas gain-of-function mutants in the same gene phenocopy the action of the drug (Guest et al, 2007). Evidence that this mode of action was conserved in parasites was recently provided by the successful expression of SLO-1 from Ancylostoma caninum and Cooperia oncophora in a slo-1 mutant of C. elegans; this restored susceptibility to the drug , whereas expression of the human form of the protein did not (Crisford et al, 2011). SLO-1 channels are highly conserved, regulating neurosecretion, hormone release, muscle contraction, and neuronal excitability (Salkoff et al, 2006), which is consistent with the multiple effects of the drug seen in vivo.…”
Section: Potassium Channelsmentioning
confidence: 95%